Bright and Early Books : In a People House - LeSieg, Theo., 1904-1991.; 1904-1991.; McKie, Roy (New York : Random House, 1972)
Easy-to-read rhyme cites a number of common household items.
Keywords: Vocabulary; Rabbits -- Juvenile fiction; Mice -- Juvenile fiction; Early readers